2001
DOI: 10.1021/jp003615r
|View full text |Cite
|
Sign up to set email alerts
|

Raman and Fluorescence Spectra of Size-Selected, Matrix-Isolated C14 and C18 Neutral Carbon Clusters

Abstract: The surface plasmon polariton-enhanced Raman spectra of size-selected, matrix-isolated C 14 neutral clusters are presented along with the calculated vibrational frequencies for the ring and linear chain isomers. The Raman spectra show resonance enhancement over a range of excitation wavelengths from 457.9 to 514.5 nm. The measured vibrational spectra are most consistent with the linear chain isomer. In addition, fluorescence spectra of neutral, mass-selected C n (n ) 14 and 18) clusters are presented. The isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
(62 reference statements)
0
27
0
Order By: Relevance
“…Optical properties of atmospheric PM such as elastic scattering, absorption, fluorescence, and Raman spectra have been used to characterize the dynamic variability, aging process, and chemical compositions of emission from biomass burning [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Studies found that scattering and absorption efficiency strongly correlated to particle size and black carbon (BC) content related to individual fire physics [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical properties of atmospheric PM such as elastic scattering, absorption, fluorescence, and Raman spectra have been used to characterize the dynamic variability, aging process, and chemical compositions of emission from biomass burning [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Studies found that scattering and absorption efficiency strongly correlated to particle size and black carbon (BC) content related to individual fire physics [14].…”
Section: Introductionmentioning
confidence: 99%
“…Black carbon concentrations in particulate organic matter from biomass burning can be deduced by observing pyrene fluorescence loss [17]. Fluorescence and Raman spectra are good methods for characterizing the natural carbon clusters [18]. Particle size, morphology, refractive index, carbon and PAH contents help understand the emissions [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…16 The Raman spectra of matrix-isolated massselected C 2n ͑7 ഛ n ഛ 10͒ were assigned to linear isomers. 17,18 However, the fluorescence spectra seen under the same conditions for C n ͑n =14,18͒ were attributed to cyclic isomers. 18 In the recent years an effort has been made by our group to obtain the electronic spectra of carbon chains, particularly in an attempt to understand which species have strong transitions in the diffuse interstellar band ͑DIB͒ region.…”
Section: Introductionmentioning
confidence: 90%
“…In general, the spectral features exhibit constant shifts with increasing chain length. The IR stretching frequencies of the NO group, for example, increase from 1630 cm -1 for 12a to the limit of 1653-1654 cm -1 for 12e-g (n = 6,8,10) due to the increasing inductive effect of the polyyne group. Not only the wavelengths of the absorption maxima but also the molar extinction coefficients increase with increasing chain length; E of the longest polyyne 12g approaches 2 q 10 5 m -1 cm -1 .…”
Section: Linear Polyynesmentioning
confidence: 99%
“…For the mass-selected anions trapped in Ne matrices, the electronic absorption spectra of C 2n -(n = 2-7) [8a, 8b] and of C 2n + 1 -(n = [2][3][4][5] [8c], and also the emission of C 4 - [9] were reported. Surface plasmon polariton-enhanced Raman spectra (SERS) were obtained for size-selected C 2n (n = 7-10) clusters in nitrogen matrices and compared with the calculated vibrational frequencies for the ring and linear chain isomers [10]. New spectroscopic information in the gas phase has also been accumulated.…”
Section: Linear Carbon Clustersmentioning
confidence: 99%